Sufi elites in central Morocco and the authority of Awliya (7th - 9th century AH / 13-15 AD) - gatel, ilhem (Journal of Social Sciences and Humanities, 2023)
It seems that the criteria of the politician, the noble lineage, the science and the criterion of wealth were not sufficient to explain the developments of the events occurring in the society of the Middle Maghreb, especially if we knew of those crises that the Islamic Maghreb as a whole suffered from; And the Central Maghreb in particular during the period from the seventh to the ninth centuries AH / 13-15 AD. Sufism takes root and strengthens its authority during crises, when weakness spreads in the entity of the central state. And strife appears alongside famines, epidemics and disasters. The intervention of Awliya at that time becomes a necessary alternative to restore the political and social balance.